Vascular Endothelial Growth Factor/Placental Growth Factor Heterodimer Levels in Preterm Infants with Bronchopulmonary Dysplasia - Procianoy, Renato S.; Hentges, Cláudia R.; Silveira, Rita C. (American Journal of Perinatology, 2016)
Background Bronchopulmonary dysplasia (BPD) is associated with changes in pulmonary angiogenesis. However, the role of the vascular endothelial growth factor/placental growth factor (VEGF/PlGF) heterodimer, an antiangiogenic factor, remains unknown in this disease.Objective To compare VEGF/PlGF levels in preterm infants with and without BPD.Methods This study was approved by the Institutional Review Board. Preterm neonates with birth weight <2,000 g and gestational age ≤34 weeks were included. Exclusion criteria were: neonates transferred from other institutions after 72 hours of life; death before blood collection; presence of major congenital malformations, inborn errors of metabolism, and early sepsis; and mothers with multiple pregnancies, TORCH infections, HIV infection, or autoimmune diseases. BPD was defined as the need for oxygen therapy for a period equal to or greater than 28 days, accompanied by radiographic changes compatible with the disease. Blood was collected from neonates in the first 72 hours of life. VEGF/PlGF levels were measured using the enzyme-linked immunosorbent assay method. The chi-square test, t-test, Mann–Whitney test, analysis of variance, and Kruskal–Wallis test were used for statistical analysis. Variables found to be significant in the univariate analysis were included in the multivariate analysis.Results Seventy-three patients were included (19 with BPD, 43 without BPD, and 11 neonates who died in the first 28 days of life), with a mean (SD) gestational age of 30.32 (2.88) weeks and birth weight of 1,288 (462) g. Median VEGF/PlGF levels were higher in the groups with BPD and death in the first 28 days of life than in the group without BPD (16.46 [IQR, 12.19–44.57] and 20.64 [IQR, 13.39–50.22], respectively, vs. 9.14 [IQR, 0.02–20.64] pg/mL], p < 0.001). Higher VEGF/P1GF levels remained associated with BPD and death in the first 28 days of life in the multivariate analysis.Conclusion Higher plasma VEGF/PlGF levels were found in preterm neonates with BPD and in those who died in the first 28 days of life, suggesting an important role of this substance in pulmonary vascular development.
Keywords: preterm neonates; VEGF/PlGF heterodimer; angiogenesis; respiratory distress syndrome; bronchopulmonary dysplasia